Transformation of Waste Management Capacity Development Through Waste Bank: Analysis of Community Empowerment Process in Nourth Bontang - Bika Nisa Luthfiana; Sri Wahyuni (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to find out the process of community empowerment in the management of the Bougenvil Waste Bank seen from: 1) awareness stage, 2) capacity stage, 3) empowerment stage and 4) factors that support and hinder community empowerment. This research is a qualitative research. Data was collected through interviews, observations, and document studies involving directors, administrators, and customers of the Bougenvil Waste Bank. Data analysis is carried out by data reduction, data presentation, and conclusion drawn. The results of the study show that the process of community empowerment in the management of the Bougenvil Waste Bank includes: 1) The awareness stage is carried out by the process of identifying needs through discussions with the community to overcome environmental problems and socializing the program by inviting the community to join as customers of the Bougenvil Waste Bank. 2) The capacity building stage is carried out by carrying out routine activities for waste collection services and providing community education programs in the form of waste sorting training activities. 3) The empowerment stage by providing post-program assistance in the form of providing continuous motivation, monitoring community development, and always reminding the community.